APP Causes Hyperexcitability in Fragile X Mice - Westmark, Cara J.; Chuang, Shih-Chieh; Hays, Seth A.; Filon, Mikolaj J.; Ray, Brian C.; Westmark, Pamela R.; Gibson, Jay R.; Huber, Kimberly M.; Wong, Robert K. S. (Frontiers in Molecular Neuroscience, 2016)
Amyloid-beta protein precursor (APP) and metabolite levels are altered in fragile X syndrome (FXS) patients and in the mouse model of the disorder, Fmr1KO mice. Normalization of APP levels in Fmr1KO mice (Fmr1KO/APPHET mice) rescues many disease phenotypes. Thus, APP is a potential biomarker as well as therapeutic target for FXS. Hyperexcitability is a key phenotype of FXS. Herein, we determine the effects of APP levels on hyperexcitability in Fmr1KO brain slices. Fmr1KO/APPHET slices exhibit complete rescue of UP states in a neocortical hyperexcitability model and reduced duration of ictal discharges in a CA3 hippocampal model. These data demonstrate that APP plays a pivotal role in maintaining an appropriate balance of excitation and inhibition (E/I) in neural circuits. A model is proposed whereby APP acts as a rheostat in a molecular circuit that modulates hyperexcitability through mGluR5 and FMRP. Both over- and under-expression of APP in the context of the Fmr1KO increases seizure propensity suggesting that an APP rheostat maintains appropriate E/I levels but is overloaded by mGluR5-mediated excitation in the absence of FMRP. These findings are discussed in relation to novel treatment approaches to restore APP homeostasis in FXS.